UPAYA GURU BIMBINGAN KONSELING DALAM MENGATASI PERILAKU MENYIMPANG BERPACARAN SISWA - Lilies Marlynda (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
This article described about the results of the study author of the teachers guidance counseling in addressing deviate behavior date students. The effort is an establishment of efforts to achieve what he will. The teachers guidance counseling in addressing deviate behavior date is a efforts to handle the situation done by educator against a series of the joint activity tinged intimacy and the interconnected emotion between men and women who has not been married in preventing behavior in the opposite sex outside the rules applicable norm. There are three efforts, these efforts include preventive measures, efforts to curative, and efforts to coach.